2002
DOI: 10.1007/s00266-002-1032-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass-Ceramics in Facial Skeleton Contouring

Abstract: The removal of certain facial-bone defects is a prerequisite to restoration of function, stability, and appearance. Synthetic bone substitutes are beneficial in cases where other operative techniques would be an unacceptable burden for a patient. Satisfactory results can be achieved in one surgical intervention with low costs and low demand on technical equipment. Osteoconductive, biocompatible, non-resorbable glass-ceramic implants based on oxyfluoroapatite and wollastonite permit osteointegration--a direct p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…These can be taken care of along with the correction of the nose and lip. 9 All principles outlined above were respected in the study group. An upper age limit of corrective intervention was deliberately not set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These can be taken care of along with the correction of the nose and lip. 9 All principles outlined above were respected in the study group. An upper age limit of corrective intervention was deliberately not set.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,10 Naturally, the demand for hard tissues to support the resulting contour needs to be considered. Autologous grafts are viewed as suitable substitutes for bone and cartilage.…”
mentioning
confidence: 99%
“…14 Patients demand maximum effect with minimum risk, negligible needed time, and low financial costs. 15 Especially patients in older age groups have a negative attitude toward complex procedures. 16 Patient selection for the reconstruction of the alveolus with the subsequent application of a dental implant must be very rigorous.…”
Section: Discussionmentioning
confidence: 99%
“…Duskova et al [46] reported an extrusion rate of 20% over a time period of 2 years for glass ceramic implants used in facial recontouring. Despite the authors’ positive resumee this complication rate seems too high.…”
Section: Bone Substitutesmentioning
confidence: 99%